Dead-time analysis of digital spectrometers - Cardoso, João M. (2004)
This paper studies the impact that the outcome of new digital architectures has brought to dead time of spectrometers. Special emphasis is given to the performance comparison between conventional spectrometers and the most important architectures usually adopted in the digital solutions. Dead-time analysis is accomplished through a dedicated numerical simulation application developed with the purpose of optimizing the digital architecture performance taking into account parameters such as the incident rate of events, the existence of pulse pile-up or the complexity of the processing algorithm used during the digital pulse processing. Results of simulations using a real time multiprocessor platform (Digital Pulse Processing-M8) are presented and design options are justified accordingly.